Non‐Surgical Treatment of Tracheal Glomus Tumour Using Rigid Fiberoptic Bronchoscopy: A Case Report - Haanieh Nasiraei Mir; Maryam Mazraehei Farahani; Arda Kiani; Somayyeh Ghadimi (Respirology Case Reports)
ABSTRACT Glomus tumours are a group of benign neoplasms originating from the modified smooth muscle cells at the arteriovenous anastomosis that can impact body temperature and blood flow. They are most commonly seen in the subungual region of the subcutaneous tissue, and less frequently seen in organs including the lung and trachea. Tracheal Glomus Tumours (TGTs) are extremely rare subtypes of primary tracheal tumours affecting patients with a mean age of 45, most commonly seen in males and presenting symptoms including cough, dyspnoea, or haemoptysis. Although surgery is considered the primary approach for the treatment of TGT, alternative approaches such as rigid fiberoptic bronchoscopy are considered especially due to the rarity of this disease. In the present case, we report a 38‐year‐old male patient with a TGT near the carina with symptoms including dyspnoea, cough, and mild haemoptysis. Although the diagnostic approaches revealed a polyploid mass, surgery was related to a higher risk of complications and thus, we used rigid fiberoptic bronchoscopy for the resection of the tumour and considered a 12‐month follow‐up for monitoring of the patient to assess the need for potential surgical treatment.